New Evidence of the Health Status and Economic Growth Relationship - Monterubbianesi, Pablo Daniel; Grandes, Martín; Dabús, Carlos (Panoeconomicus, 2017)
Over the last two decades, the role of health as a determinant of growth has been gaining ground in economic analysis due to longer average life expectancy at birth or lower infant mortality experienced in developing and fast-growing emerging economies. The empirical approach to this problem, based primarily on econometric analysis, has focused on two alternative approaches; the growth accounting models and the "a la Barro" regressions. This study aims to measure the contribution of health to economic growth using a panel of 91 countries over the period 1960-2005, and to compare the estimated impact of better health status on long-run per capita income under those two approaches, controlling for potential endogeneity. Our main results show the marginal effect of the change in health status in the long-term income lies between 2.6% in the growth accounting models and 8.3% in the "a la Barro" regressions. These results are consistent with the marginal effects we simulate and quantify using the health-growth point estimates found in earlier literature. Key words: Health status, Economic growth, Long-run income, Growth account, “A la Barro” regressions. JEL: I15, O47. U poslednje dve decenije uloga zdravlja kao determinanta rasta postaje osnova u ekonomskoj analizi zbog dužeg prosečnog očekivanog životnog vieka pri rođenju ili niže smrtnosti novorođenčadi u zemljama u razvoju i razvijenim zemljama. Empirijski pristup ovom problemu, zasnovan pre svega na ekonometrijskoj analizi, fokusiran je na dva alternativna pristupa; modeli predviđanja rasta i regresije “a la Barro”. Ova studija ima za cilj da meri doprinos zdravlja ekonomskom rastu koristeći panel od 91 zemlje tokom perioda 1960-2005 i da uporedi procenjeni uticaj boljeg zdravstvenog statusa na dugoročni prihod po glavi stanovnika u okviru ova dva pristupa, kontrolišući potencijalnu endogenost. Naši glavni rezultati pokazuju da je marginalni efekat promene zdravstvenog stanja u dugoročnom prihodu leži između 2,6% u modelima predviđanja rasta i 8,3% u regresiji “a la Barro”. Ovi rezultati su u skladu sa marginalnim efektima koje simulišemo i kvantifikujemo pomoću procena toka zdravstvenog rasta u ranijoj literaturi. Ključne reči: zdravstveni status, ekonomski rast, dugoročni prihod, predviđanje rasta, “a la Barro” regresije.